PEMBELAJARAN MODEL KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA KEMAMPUAN PEMECAHAN MASALAH MATERI PECAHAN SISWA KELAS IV SD - Abdul Rahman; Sylvia Rabbani (IKIP Siliwangi, 2021)
This study aims to determine efforts to improve mathematics learning achievement using cooperative learning model Student Team Achievement Division four grade students of elementary Plus Al-Aitaam and the application of STAD cooperative learning model to improve student’s problem solving skills. STAD cooperative learning model is a learning technique cooperative which invites students to discuss, help each other and work together to accomplish tasks of teachers. Cooperative learning model STAD can also train students in the skills of working and completing tasks assigned by the teacher. Applied research by researchers is a class action. Subjects were students of class IV SD Plus Al-Aitaam totaling 30 students. The instrument used for this study is a short essay test prepared by the researchers. The data analysis technique used is qualitative descriptive techniques, to examine the data that is by collecting student test results, convert raw scores into grades so, finding the average and compared with that of the previous conditions. The experiment was conducted in tri meeting. Based on the results of research and of the discussion on this research, it can be deduced that there is the representation of the student mathematical 4rd class especially on math material floating STAD after enactment of the model.